Bioaccumulation of Polychlorinated Dibenzo-p-Dioxins (PCDDs) and Dibenzofurans (PCDFs) in Hediste diversicolor (Polychaeta: Nereididae) - Picone, Marco; Delaney, Eugenia; Tagliapietra, Davide; Guarneri, Irene; Volpi Ghirardini, Annamaria (Frontiers in Ecology and Evolution, 2020)
The effectiveness and reliability of the polychaete Hediste diversicolor (O.F. Müller, 1776) to bioaccumulate polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) was assessed in an in-situ passive biomonitoring study. Field collected specimens were sampled in 5 sites within the Venice Lagoon (Italy), selected along a PCDD/F contamination gradient. The homologue profiles in the tissues of the common ragworm were considerably different from those observed in the sediments, independent of sediment contamination. Moreover, H. diversicolor accumulated preferentially the less chlorinated 2,3,7,8-TCDD, 2,3,7,8-TCDF and 2,3,4,7,8-PeCDF compared to the more chlorinated and hydrophobic hexa-, hepta- and octa-substituted congeners, as evidenced by the significant and linearly decreasing trend of the Biota-to-Sediment Accumulation Factor (BSAF) with the increasing lipophilicity of the congeners, expressed as the logarithmic form of the octanol/water partition coefficient (logKOW). The BSAFs for dioxins and furans were generally low compared to other organochlorine compounds such as polychlorinated biphenyls and organochlorine pesticides, suggesting that H. diversicolor may eliminate both dioxins and furans efficiently.